Assessment of intuitive eating in Saudi Arabia and its relationship with sociodemographic factors and nutritional indicators using an Arabic version of the Intuitive Eating Scale-2 - Albajri, Eram; Naseeb, Manal (Frontiers in Nutrition, 2025)
BackgroundIntuitive eating (IE) is an eating style where the person responds to the bodily signals of satiety and hunger. This study assessed IE in Saudi Arabia using the newly validated Saudi Arabic Intuitive Eating Scale 2 (IES-2). It also examined the influence of sociodemographic factors, sex, and BMI on the scale and subscale scores.MethodsThis cross-sectional study gathered data online, using the Saudi Arabic IES-2, from individuals aged 18 years and older with a BMI of 18.5 kg/m2 or higher residing in Saudi Arabia.ResultsThere were 387 respondents (57.9% women) with an average age of 31.83 ± 11.06 years. BMI showed a significant negative association with the total scale and subscale scores (p < 0.05). The total IE score was significantly influenced by age, sex, BMI, educational level, employment status, and recent weight change. Sex specifically affected the scores for the “Eating for Physical Rather than Emotional Reasons “(EPR) and “Reliance on Hunger and Satiety Cues for Eating subscales” (RHSC). Employment status was a significant predictor for the RHSC subscale score. Age and recent weight change specifically influenced the Unconditional Permission to Eat subscale score.ConclusionOur findings emphasize the multidimensional impact of sociodemographic factors on IE behaviors among Saudis, and the importance of culturally customized interventions to promote IE practices in the region. Preliminary findings support the promotion of IE in public health and prevention initiatives. Future research should explore the longitudinal relationships and intervention strategies aimed at enhancing IE practices.